Implementasi Pendidikan Islam Rahmatan Lil Alamin Sejak Dini pada Pemuda Milenial di Indonesia dalam Mencegah Dampak Negatif Westernisasi - Mohamad Yamin; Dodo Suhada; Uus Ruswandi; Mohamad Erihadiana (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to reveal how the application of rahmatan lil 'alamin Islamic education from an early age to millennial teenagers in Indonesia in order to prevent the negative impact of westernization. The research method uses a literature review, in which the primary sources are various books, journals, internet, and other relevant sources about Westernization. Where westernization is actually an effect of globalization, it is important for millennials in Indonesia to understand this, where the impact of this westernization has positive and negative impacts. The results of the study indicate that in the application of rahmatan lil'alamin Islamic education in Indonesia in order to prevent the negative impact of Westernization caused by the west (the effect of globalization), it can be prevented by applying character education as early as possible to millennial youth in Indonesia, as well as instilling Rahmatan Lil 'Alamin's Islamic education from an early age.